The Effect of Workload, Work Stress, Autocratic Leadership Style On Employee Satisfaction (Study at PT. Angkasa Pura Administrative Division of I Gusti Ngurah Rai Airport Branch Office Denpasar Bali) - Juliati, Ratih; Aprillian Zulfiqar. P, Anas; Shafiraa, Ratya (Manajemen Bisnis, 2024)
This study aims to analyze the influence of workload, work stress, and autocratic leadership style on employee job satisfaction at PT Angkasa Pura, I Gusti Ngurah Rai Airport Branch Office. Utilizing a quantitative approach, this research involved 53 employees from the Administration division as the sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The study also included instrument validity testing, classical assumption testing, and hypothesis testing. The results indicate that workload, work stress, and autocratic leadership style have a significant and positive impact on job satisfaction. Employees' ability to manage high workloads contributes to increased satisfaction. Effective work stress management further enhances job satisfaction. Additionally, the implementation of an appropriate autocratic leadership style positively influences employees' overall job satisfaction.